2015
DOI: 10.1126/scitranslmed.aaa4306
|View full text |Cite
|
Sign up to set email alerts
|

STING agonist formulated cancer vaccines can cure established tumors resistant to PD-1 blockade

Abstract: Stimulator of interferon genes (STING) is a cytosolic receptor that senses both exogenous and endogenous cytosolic cyclic dinucleotides (CDNs), activating TBK1/IRF3 (interferon regulatory factor 3), NF-κB (nuclear factor κB), and STAT6 (signal transducer and activator of transcription 6) signaling pathways to induce robust type I interferon and proinflammatory cytokine responses. CDN ligands were formulated with granulocyte-macrophage colony-stimulating factor (GM-CSF)–producing cellular cancer vaccines—termed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
547
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 600 publications
(563 citation statements)
references
References 44 publications
13
547
1
2
Order By: Relevance
“…We therefore hypothesize that smoking signature-high HNSCC may benefit from immune modulators such as IL-2, TLR, and STING agonists used in other cancer types to boost overall host immunity. This may facilitate the response to checkpoint blockade, similar to results in other recent studies (76). It is possible that checkpoint blockade alone could potentially drive increased immune infiltration in smoking signature-high tumors in a chemokine-dependent fashion.…”
Section: Discussionsupporting
confidence: 66%
“…We therefore hypothesize that smoking signature-high HNSCC may benefit from immune modulators such as IL-2, TLR, and STING agonists used in other cancer types to boost overall host immunity. This may facilitate the response to checkpoint blockade, similar to results in other recent studies (76). It is possible that checkpoint blockade alone could potentially drive increased immune infiltration in smoking signature-high tumors in a chemokine-dependent fashion.…”
Section: Discussionsupporting
confidence: 66%
“…The 2′,3′ mixed linkage structure confers increased STING binding affinity (52) and is also found in endogenous cGAMP produced by eukaryotic cGAS. ML RR-S2 CDA was shown to broadly activate all known human STING alleles in a HEK293T cellular STING signaling assay and induced dose-dependent expression of IFN-β in human peripheral blood monocytes (PBMCs) isolated from multiple donors with different STING genotypes, including a donor homozygous for the REF allele, which is known to be refractory to signaling induced by bacterial 3′,3′ CDNs (8,86). ML RR-S2 CDA was evaluated in multiple syngeneic mouse tumor models, including B16.F10 melanoma, 4T1 mammary carcinoma, and CT26 colon carcinoma, and demonstrated a potent antitumor immune response and significant tumor regression in each model (8).…”
Section: Pharmacological Use Of Sting Agonistsmentioning
confidence: 99%
“…It became possible to test the effects of STING activation when it was discovered that the cells, and induced more potent antitumor immunity compared with CDNs that did not contain a dithio modification (8,86). To increase affinity for human STING, ML RR-S2 CDA contains a noncanonical structure defined by a phosphate bridge with one 2′-5′ and one 3′-5′ mixed phosphodiester linkages (2′,3′ CDNs).…”
Section: Pharmacological Use Of Sting Agonistsmentioning
confidence: 99%
“…Of note, other mechanistically similar strategies using adjuvant-like immunostimulators (such as STING pathway agonists) have been reported to sensitize tumors to subsequent immune checkpoint blockade, further strengthening the argument for such a combinatorial approach. 14 , 15 Similarly, it has been shown that immunogenic cell death (ICD) inducers such as oxaliplatin and cyclophosphamide sensitize KRAS-induced lung cancers to subsequent immune checkpoint blockade. 16 It is not unreasonable to postulate that viruses, in particular T-VEC, can induce ICD because T-VEC has been genetically modified to remove genes that suppress the immune response and accentuate the premortem stress responses, including the type-1 interferon response, that characterize ICD.…”
mentioning
confidence: 99%